EXPLORING THE ROLE OF TECHNOLOGY INTEGRATION IN TWENTY-FIRST CENTURY EDUCATION - Emilya Zeynalova Faig (International Journal of Innovative Technologies in Social Science, 2023)
In today's 21st century, as technology-integration has become the focus of debates about changing instructor methodology. This paper looks briefly at how changes in educational trends have created a new landscape for instructors and learners alike. Therefore, this study attempts to explore the multifaceted role of technology in classrooms and their impact on teaching-learning. One goal is to examine how well technology has made itself part of everyday life and education, what opportunities this reality brings yet also the pitfalls; We'll showcase instances along with an evaluation to determine their level of educational significance.